2020
DOI: 10.1111/gbi.12393
|View full text |Cite
|
Sign up to set email alerts
|

In situ S‐isotope compositions of sulfate and sulfide from the 3.2 Ga Moodies Group, South Africa: A record of oxidative sulfur cycling

Abstract: Sulfate minerals are rare in the Archean rock record and largely restricted to the occurrence of barite 5 (BaSO 4). The origin of this barite remains controversially debated. The mass-independent fractionation 6 of sulfur isotopes in these and other Archean sedimentary rocks suggests that photolysis of volcanic 7 aerosols in an oxygen-poor atmosphere played an important role in their formation. Here we report 8 on the multiple sulfur-isotopic composition of sedimentary anhydrite in the ca. 3.22 Ga Moodies Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 82 publications
(261 reference statements)
2
6
0
Order By: Relevance
“…Bladed and granular barite is characterized by δ 18 O and δ 34 S values that fall within the range reported for Paleoarchean seawater sulfate from sulfate minerals and carbonate-associated sulfate (Fig. 1b, 1c) 15,26,41,42 . Seawater-like δ 18 O and δ 34 Table S2).…”
Section: Does Barite Re Ect Seawater?supporting
confidence: 79%
See 1 more Smart Citation
“…Bladed and granular barite is characterized by δ 18 O and δ 34 S values that fall within the range reported for Paleoarchean seawater sulfate from sulfate minerals and carbonate-associated sulfate (Fig. 1b, 1c) 15,26,41,42 . Seawater-like δ 18 O and δ 34 Table S2).…”
Section: Does Barite Re Ect Seawater?supporting
confidence: 79%
“…Previous work has demonstrated that the magnitude of seawater sulfate D 33 S decreases throughout the Paleoarchean, as shown in Fig. 1d 26,27,42 . The observed correlation between Sr and S isotopes in bladed barite is therefore best explained by co-evolution of D 33 51,52 and hydrothermal uid (150°C) that lead to oversaturation with respect to barite 53 .…”
Section: Does Barite Re Ect Seawater?mentioning
confidence: 69%
“…Under higher sulfate conditions, microbial sulfate reduction results in S isotope fractionations up to 45 per mil (‰) ( 44 ), and several Archean deposits exhibit large S isotope fractionations, suggesting locally high sulfate concentrations ( 45 , 46 ). For example, the pyrite in the Hemlo gold deposit in Wawa, Ontario, shows δ 34 S values ranging from −17.5 to +12.6‰ ( 45 ), and the Dresser Formation in North Pole ( 46 ) and the Moodies Group in Barberton Greenstone Belt, Africa, show fractionations up to 21.1 and 34‰, respectively ( 47 ). All three of these locations also contain sulfate minerals such as barite and anhydrite.…”
Section: Discussionmentioning
confidence: 99%
“…These types of environments could have had extensive Fe 3+ -mediated pyrite dissolution due to the shallow water depth that allowed light penetration and Fe 2+ photooxidation. Moreover, Archean pyrites are known to contain mass-independent fractionation S isotope signals ( 7 , 8 , 14 , 47 , 48 ), and the dissolution of these pyrites should release sulfate with Δ 33 S anomalies inherited from the pyritic sulfur. Currently, it is unknown whether UV-driven sulfate production from pyrite oxidation causes additional isotope fractionations that might be discernable in the Archean geologic record.…”
Section: Discussionmentioning
confidence: 99%
“…Features related to evaporite relics consist of lenticular biterminated crystal and isolated/coalesced nodular features with acicular-lath crystals (Figure 3.10). These features are associated with gypsum or anhydrite phase formed in the surface environment and require a sulfate enrichment process such as evaporative brine formation or oxidative sulfide weathering (Nabhan et al, 2020). Indeed, barite (as well as carbonate) appears as a substitute for likely calcium sulfate phases (Figure 3.10).…”
Section: -Origin Of Barite At Avellaneda Formationmentioning
confidence: 99%